Use of platelet and erythroid growth factors during induction chemotherapy for acute lymphoblastic leukaemia in a Jehovah's Witness. Issue 1 (7th December 2018) - Arora, Nivedita; Gupta, Arjun; Li, Hsiao C; Sadeghi, Navid
Abstract : We present a 21-year-old woman diagnosed with Philadelphia (Ph) chromosome-like CD20 positive B-cell acute lymphoblastic leukaemia (ALL). She was a Jehovah's Witness (JW) and declined all blood product transfusion support. She was initiated on the CALGB 10403 chemotherapy protocol for her ALL. She received darbepoetin alfa and romiplostim as supportive therapies for her disease/chemotherapy-associated anaemia and thrombocytopaenia. A complete remission was achieved with negative minimal residual disease and she remains in remission 18 months after diagnosis. This case report describes the successful treatment of an adult JW with Ph-like CD20 +B cell ALL, in the absence of blood product transfusions, using growth factor support.